Community Empowerment in Teluk Awur Jepara Village through the Ecopreneurship Training-Flavoring Production from the Prawn Husk - Susanti, Siti; Martono, Kurniawan Teguh; Mulyani, Sri; Al-Baarri, Ahmad Ni’matullah (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
During the last decades, prawns have become an important sea commodity along the north coast of Java Island. The Marine Science Techno Park (MSTP) was known as the largest prawn pond in Jepara Regency give a good opportunity for surrounded people to create or develop the prawn based business. Although prawn is the good protein source, its utilization in the industrial food often resulted the organic waste especially husk. Community empowerment which was carried out in Teluk Awur Village-Jepara aimed to provide the ability and skill of people around the MSTP about processing of the prawn husk into the natural flavoring. Prawn husk flavoring (PHF) was economically viable and can be a business opportunity. Materials, production, packaging, and distribution process.